Anlotinib in recurrent or metastatic endometrial cancer. Issue 9 (23rd May 2022) - Cui, Qingli; Mao, Yuefeng; Hu, Yanhui; Ma, Dongyang; Liu, Huaimin
Abstract : Objective: For recurrent or metastatic endometrial cancer after second-line treatment, therapeutic options are limited. Anlotinib is a new multi-targeted tyrosine kinase inhibitor of tumor angiogenesis and growth. The aim of this study was to explore the efficacy and safety of anlotinib in patients with recurrent or metastatic endometrial cancer. Methods: Patients with recurrent or metastatic endometrial cancer who received anlotinib or anlotinib plus pembrolizumab after second-line treatment between July 2017 and October 2020 were analyzed. Objective response rate, disease control rate, progression-free survival, overall survival, and safety were evaluated. Results: A total of 56 patients were analyzed. The median age was 62 years (range 42–80). The median treatment of anlotinib was 5.9 cycles (range 2–21). The overall objective response rate was 42.9%, and the disease control rate was 75%. 44 (78.6%) patients received anlotinib monotherapy and 12 (21.2%) patients received anlotinib plus pembrolizumab. The objective response rate was 40.9% versus 50% (p=0.52) and the disease control rate was 72.7% versus 83.3% (p=0.59) in the monotherapy group and the combination therapy group, respectively. The median progression-free survival and overall survival from initiation of anlotinib therapy was 6 months (95% CI 4.89 to 7.11) and 13.3 months (95% CI 9.94 to 16.61), respectively. On multivariable Cox analysis, age (>60 vs ≤60 years) was an independent impact factor for both progression-free survival and overall survival, while prior lines of treatment (2 lines vs ≥3 lines) was an independent predictor of progression-free survival. The incidences of grade 3/4 adverse events were hypertension (10.7%), fatigue (7.1%), hand-foot syndrome (7.1%), proteinuria (3.6%), sore throat (3.6%), and hypothyroidism (3.6%). Conclusion: Anlotinib is effective and well tolerated in patients with recurrent or metastatic endometrial cancer. It may be considered a choice for patients younger than 60 years and who have had <3 lines of treatment.